2015
DOI: 10.1007/s00213-015-3917-y
|View full text |Cite
|
Sign up to set email alerts
|

2-AG promotes the expression of conditioned fear via cannabinoid receptor type 1 on GABAergic neurons

Abstract: Our findings suggest that increased AEA levels mediate acute fear relief, whereas increased 2-AG levels promote the expression of conditioned fear primarily via CB1 on GABAergic neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 96 publications
11
82
2
1
Order By: Relevance
“…It was described, for example, that low doses of a CB1 agonist induced anxiolytic-like effects dependent on glutamatergic neuron-located CB1 receptors, whereas anxiogenic-like effects of high doses of CB1 agonist were dependent on GABAergic neuron-located CB1 receptors (Rey et al, 2012). Moreover, in fear conditioning paradigms it was reported that deletion of CB1 receptors on glutamatergic neurons increases freezing behavior, whereas CB1 deletion on GABAergic neurons decreases it (Llorente-Berzal et al, 2015;Metna-Laurent et al, 2012). These results suggest that CB1 receptors present in GABAergic neurons are also important for modulation of a conditioned emotional response, since they could counteract effects of CB1 present in glutamatergic neurons.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was described, for example, that low doses of a CB1 agonist induced anxiolytic-like effects dependent on glutamatergic neuron-located CB1 receptors, whereas anxiogenic-like effects of high doses of CB1 agonist were dependent on GABAergic neuron-located CB1 receptors (Rey et al, 2012). Moreover, in fear conditioning paradigms it was reported that deletion of CB1 receptors on glutamatergic neurons increases freezing behavior, whereas CB1 deletion on GABAergic neurons decreases it (Llorente-Berzal et al, 2015;Metna-Laurent et al, 2012). These results suggest that CB1 receptors present in GABAergic neurons are also important for modulation of a conditioned emotional response, since they could counteract effects of CB1 present in glutamatergic neurons.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, deletion of CB1 receptors in glutamatergic neurons increases freezing behavior during re-exposure to the conditioned stimulus (Kamprath et al, 2009;Llorente-Berzal et al, 2015;Metna-Laurent et al, 2012). In the dlPAG, glutamatergic neurotransmission has an essential role in the defensive response (Carobrez et al, 2001); whereas NMDA administration induces flight reactions (Aguiar M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in strong contrast to the CB1R-dependent control of anxiety behaviour, which was in large part rescued when CB1R was re-expressed (see above). CB1R deficiency in forebrain GABAergic neurons does not seem to have an essential role in the reduction of conditioned freezing responses 86 , although a recent study reported decreased freezing in GABAergic-specific CB1R mutants on the first re-exposure to the conditioned stimulus 87 . Further support for a role of CB1R in GABAergic interneurons comes from evidence that fear extinction can cause specific remodelling of perisomatic inhibitory synapses in the basal amygdala, including alterations in the localization of the CB1R on CCK-positive neurons in this region 88 .…”
Section: Fear Behaviourmentioning
confidence: 93%
“…Activation of CB 1 Rs produces anxiolytic effects in various models of unconditioned fear, relevant to multiple anxiety disorder symptom domains (reviewed in [30][31][32][33]). Regarding conditioned fear, the effect of CB 1 R activation is complex: CB 1 R activation may enhance or reduce fear expression, depending on brain locus and the eCB ligand [34]; however, CB 1 R activation potently enhances fear extinction [35], and can prevent fear reconsolidation. Genetic manipulations that impede CB 1 R activation are anxiogenic [35], and individuals with eCB system gene polymorphisms that reduce eCB tonefor example, FAAH gene polymorphisms-exhibit physiological, psychological, and neuroimaging features consistent with impaired fear regulation [36].…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%